Transformational Leadership and Job Satisfaction: Mitigating Organizational Politics to Innovative Work Behavior - Pradana, I Putu Yoga Bumi; Sayrani, Laurensius Petrus; Pah, Theny Intan Berlian Kurniati; Rijoly, Jacobus Cliff Diky; Gusmao, Fernando Dias (Universitas Muhammadiyah Yogyakarta, 2026)
This study investigated the relationships among perceived organizational politics (POP), transformational leadership (TL), innovative work behavior (IWB), and job satisfaction (JS) in the public sector, with JS as a mediating variable. Using a quantitative approach, data were collected from 657 civil servants of the Kupang City Government using a validated, closed-ended questionnaire on a five-point Likert scale. Structural Equation Modeling (SEM) was employed to analyze the proposed relationships. The results disclosed that perceived organizational politics had a significant negative effect on job satisfaction (β = −0.211, p < 0.001) and innovative work behavior (β = −0.247, p < 0.001). In contrast, transformational leadership demonstrated a strong positive influence on job satisfaction (β = 0.684, p < 0.001) and a positive direct effect on innovative work behavior (β = 0.222, p < 0.001). Job satisfaction also significantly enhanced innovative work behavior (β = 0.223, p < 0.001). Mediation analysis indicated that job satisfaction partially mediated the relationship between perceived organizational politics and innovative work behavior (indirect effect β = −0.047, p = 0.001) and between transformational leadership and innovative work behavior (indirect effect β = 0.153, p < 0.001). These findings suggest that job satisfaction plays a crucial role in buffering the negative consequences of organizational politics and strengthening the positive impact of transformational leadership on innovation. This study contributes to public sector innovation literature by empirically demonstrating how leadership and job attitudes shape innovative behavior within a politically nuanced bureaucratic context.